(untitled) (University of Khartoum Engineering Journal, 2022)
Multiple injuries and fatalities occur during confined space entry work more than any other type of work performed in all developed countries. This research aimed at evaluating employee’s awareness of confined spaces basic concepts and work hazards, and to generally assess the entry program used to access these confined spaces. The data were collected from a random sample of factories and industries in Khartoum north industrial area. A questionnaire was the instrument used to collect the data. The data were analyzed using standard Statistical Package for the Social Sciences (SPSS). The results demonstrated lack of employee’s awareness regarding the concept of confined spaces and hazards of working. It also shows failure of (80%) of workplaces to conduct confined space training, ensure supervision and provide procedures reinforcing the need for a comprehensive confined space safety program. It also demonstrated little evidence of a safe system of work in many of the cases. Over (82%) of the confined spaces were permitted to be entered without pre-entry hazards identification. In addition no atmospheric gases monitoring before or during entry (0%) since over (80%) of spaces expected to contain atmospheric hazards depending on confined space location, construction, condition, and work to be performed. also no effective nor adequate emergency rescue procedures were hold. The results showed that the most important reasons for confined spaces accidents and fatalities were lack of employees’ perception of hazards from working in confined spaces, and scarcity of designing appropriate preventive measures and entry written programs by companies. Accordingly, the study will help in putting the companies comply with their own procedures and practices, and to maintain the safety of the employees.